A new method for design and calculating the mechanical properties and energy absorption behavior of cellular structures using foam microstructure modeling based on Laguerre tessellation. (February 2022) - Shiravand, Ali; Asgari, Masoud
Abstract: In this paper, the elastic modulus and energy absorption behavior of cellular structures such as aluminum foams have been investigated. The main purpose of this study is to develop microstructure modeling of cellular structures and to study their elastic–plastic behavior through finite element method. In this research, first a unit cell is prepared to reduce numerical calculations, which has the characteristics of the main foam. The behavior of the unit cell under impact is then simulated and analyzed by the finite element method. Using simulated experiments, a model using the response surface method to obtain the densification strain, elastic modulus, mean plastic stress, yield stress as well as foam compaction behavior will be presented. Finally, the results of finite element and response surface methods for cellular structures with experimental results is validated. The results of this study showed that the possibility of modeling and analysis of energy absorption (impact) of foams is possible using the response surface model presented in this study and finally a suitable model can be achieved to analyze the microstructure of different foams. As a consequence, the hybrid cellular structures are simulated in view of applications of foams as filler in the thin-walled structures about energy absorption subject.